2016
DOI: 10.1007/s00381-016-3217-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of selected cytokines in the etiopathogenesis of intraventricular hemorrhage in preterm newborns

Abstract: Proinflammatory cytokines are essential mediators and indicators of an inflammatory process occurring in the body. Their physiological role is to stimulate the immune response, yet their excessive propagation and interaction with cells outside the immune system may be linked to the risk of organ damage. This is specifically important in the case of immature tissues of fetuses and prematurely born infants. Analysis of the concentrations of specific cytokines in different compartments makes it possible to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
0
19
0
4
Order By: Relevance
“…Pregnancies complicated by conditions associated with increased inflammation, such as chorioamnionitis, pPROM, and prolonged rupture of membranes (ROM), have been linked to an increased risk of IVH (21)(22)(23)(24). It has been suggested that pro-inflammatory cytokines, in particular, may play a role in the development of IVH (25)(26)(27). The etiopathogenesis of IVH is complex, but evidence suggests that inflammatory processes may play a significant role.…”
mentioning
confidence: 99%
“…Pregnancies complicated by conditions associated with increased inflammation, such as chorioamnionitis, pPROM, and prolonged rupture of membranes (ROM), have been linked to an increased risk of IVH (21)(22)(23)(24). It has been suggested that pro-inflammatory cytokines, in particular, may play a role in the development of IVH (25)(26)(27). The etiopathogenesis of IVH is complex, but evidence suggests that inflammatory processes may play a significant role.…”
mentioning
confidence: 99%
“…Imperfect autoregulation of cerebral blood flow (CBF) (7) and increased serum level of interleukins (ILs: interlukin-1 beta, interlukin-6, interlukin-8, interlukin-18) and tumor necrosis factor-alpha were observed to be linked with severe IVH in extremely premature infants and are associated with neurodevelopmental disorders in this group (8)(9)(10)(11) Mean platelet volume (MPV) as an accessible predictive marker in thromboembolic events such as strokes and acute myocardial infarction in adults has already been studied (12)(13)(14). Destruction of platelets in the periphery increases the production of platelets by bone marrow that leads to an increase in the number of immature platelets in the circulatory system, thus leading to high MPV (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Although increased levels of TGF-β1 have been implicated in white matter injury in the setting of IVH and PHH, Heep et al [ 11 ] contrarily found no significant difference. A recent review by Szpecht et al [ 29 ] on the role of cytokines in the pathogenesis of IVH suggested an association between IL-1β, IL-6, IL-8, and TNF-α with increased risk of PHH [ 12 , 13 , 30 ].…”
Section: Discussionmentioning
confidence: 99%